Louis XVI and the French Revolution, 1789-1792 - Caiani, Ambrogio A. (Cambridge University Press, 2012)
"The experience, and failure, of Louis XVI's short-lived constitutional monarchy of 1789-1792 deeply influenced the politics and course of the French Revolution. The dramatic breakdown of the political settlement of 1789 steered the French state into the decidedly stormy waters of political terror and warfare on an almost global scale. This book explores how the symbolic and political practices which underpinned traditional Bourbon kingship ultimately succumbed to the radical challenge posed by the Revolution's new 'proto-republican' culture. While most previous studies have focused on Louis XVI's real and imagined foreign counterrevolutionary plots, Ambrogio A. Caiani examines the king's hitherto neglected domestic activities in Paris. Drawing on previously unexplored archival source material, Caiani provides an alternative reading of Louis XVI in this period, arguing that the monarch's symbolic behaviour and the organisation of his daily activities and personal household were essential factors in the people's increasing alienation from the newly established constitutional monarchy"--